2014
DOI: 10.1111/jfq.12103
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Chemical Composition and Quality‐Related Characteristics in Bread Making with Wheat Flour–Fine Bran Blends

Abstract: The present study investigated the relationships between chemical composition and bread-making quality parameters of white flour substituted with 30% of fine bran from two wheat genotypes. Fine bran with particle diameters ranging from 265 to 155 μm was sifted into two fractions (265-180 and 180-155 μm) and was studied in an experiment with a full factorial design. Each fine bran fraction with its natural chemical composition was found to have a significant effect on bread volume and texture, achieving higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…But when compared to whole wheat flour bread, the hardness of bread with ultrafine WB was lower. Increase in dough consistency and decrease in dough strength were reported for bread dough containing 30% fine bran particle sizes ranging from 155 to 265 lm (Pavlovich-Abril et al, 2015). Extrusion has been shown to increase the total dietary fibre content of WB.…”
Section: Wheat Bran Functionality In Wheat Doughmentioning
confidence: 99%
See 1 more Smart Citation
“…But when compared to whole wheat flour bread, the hardness of bread with ultrafine WB was lower. Increase in dough consistency and decrease in dough strength were reported for bread dough containing 30% fine bran particle sizes ranging from 155 to 265 lm (Pavlovich-Abril et al, 2015). Extrusion has been shown to increase the total dietary fibre content of WB.…”
Section: Wheat Bran Functionality In Wheat Doughmentioning
confidence: 99%
“…It has been suggested that the effect of WB fibre in dough is more than just dilution or interference with gluten network, but rather a fibre-protein interaction (Anil, 2012). Medium-sized bran particles (415 lm) may increase loaf volume, while coarse WB significantly decreases loaf volume (Pavlovich-Abril et al, 2015). Furthermore, functionality of WB is affected by treatment processes.…”
Section: Wheat Bran Functionality In Wheat Doughmentioning
confidence: 99%
“…There are various wheat bran‐based supplements in the market which are used to lose weight. There are also wheat bran‐based breads (Almeida, Chang, & Steel, 2013; Pavlovich‐Abril, Rouzaud‐Sández, Romero‐Baranzini, Vidal‐Quintanar, & Salazar‐García, 2015), muffins, cookies, and flakes available in the market as these products are a healthier alternative and simultaneously prevent or control many CVDs such as diabetes, hypertension. Moreover, wheat bran has been used to develop pasta (Kim, Cho, Chun, & Park, 2013; Sobota, Rzedzicki, Zarzycki, & Kuzawińska, 2015), noodles (Song, Zhu, Pei, Ai, & Chen, 2013), and doughnut (Kim, Chun, Cho, & Park, 2012) to increase the nutritional and functional value of the product.…”
Section: Market Potential and Applications Of Wheat Bran And Rice Branmentioning
confidence: 99%
“…There is an opinion that FHC and FBС are determined by lignin presence and independent from its particles size [1,2]. Some authors [3][4][5][6] showed the dependence of fat holding and binding capacities on the number and size of the raw material particles. This suggested that the mechanism of fat absorption by the food fibers can be determined not only by the lignin sorption activity, the efficiency of which increases when grinding, but also by the surface adsorption [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The numerous studies show that the structure peculiarities and the presence of hydrophobic groups contribute to the fat binding by the raw material components [3][4][5][6][7][8]. By the experimental studies the good FHC was found for citrus fibers Herbacel AQ Plus, type N and Citrifi; carrageenans; carob bean, guar and xanthan gums [7][8][9]; the egg powder, the milk powder and the dairy foods; wheat, soya, oatmeal and pea flour [7,9,10]; various functional ingredients derived from the industrial by-products (skin, hoof, feathers, by-products, etc.)…”
Section: Introductionmentioning
confidence: 99%